2023
DOI: 10.2147/jmdh.s398997
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Single and Combined Schemes of Asia-Pacific Colorectal Screening, Faecal Immunochemical and Stool Deoxyribonucleic Acid Testing for Community Colorectal Cancer Screening

Abstract: Objective To compare the screening efficacy of colonoscopy and pathologically confirmed single and combined Asia-Pacific colorectal screening (APCS), faecal immunochemical testing (FIT) and stool deoxyribonucleic acid (sDNA) testing protocols. Methods From April 2021 to April 2022, 842 volunteers participated in primary colorectal cancer (CRC) screenings using APCS scoring, FIT and sDNA testing and 115 underwent a colonoscopy. One hundred high-risk participants were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…In a previous study, the combination of FIT and sDNA tests obtained a sensitivity of about 50.00% for precancerous lesions. 6 In the present study, most of the positive cases we enrolled were LGIN. We found that the AUC of our prediction model for predicting positive colonoscopy results was much higher than that of the FIT + sDNA test scheme.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In a previous study, the combination of FIT and sDNA tests obtained a sensitivity of about 50.00% for precancerous lesions. 6 In the present study, most of the positive cases we enrolled were LGIN. We found that the AUC of our prediction model for predicting positive colonoscopy results was much higher than that of the FIT + sDNA test scheme.…”
Section: Discussionmentioning
confidence: 71%
“…In our previous study, sDNA test using methylated SDC2 exhibited better sensitivity than FIT for detecting LGIN, AA and advanced colorectal neoplasia. 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations